Insights into the effects of bromide at fresh water levels on the radical chemistry in the UV/peroxydisulfate process. (1st June 2021) - Wang, Anna; Hua, Zhechao; Wu, Zihao; Chen, Chunyan; Hou, Shaodong; Huang, Bangjie; Wang, Yuge; Wang, Ding; Li, Xuchun; Li, Chuanhao; Fang, Jingyun
Highlights: Br − converts SO4 − to HO and bromine radicals and also scavenges HO in UV/PDS. Bromine radicals are much higher than SO4 − and HO at pH 7 but lower at pH 10. Cl − and Br − converts SO4 − to HO but chlorine radicals are negligible. Br − at several μM levels promote some micropollutant degradation in UV/PDS. Abstract: Bromide (Br − ) is a typical scavenger to sulfate radical (SO4 − ) and hydroxyl radical (HO ), which simultaneously forms secondary reactive bromine species (RBS) such as Br and Br2 − . This study investigated the effects of Br − at fresh water levels ( μM) on the radical chemistry in the UV/peroxydisulfate (UV/PDS) process by combining the degradation kinetics of probe compounds (nitrobenzene, metronidazole, and benzoate) with kinetic model. Br − at 1 − 50 μM promoted the conversion from SO4 − to HO and RBS in the UV/PDS process. At pH 7, the concentration of SO4 − monotonically decreased by 31.5 – 94.8% at 1 – 50 μM Br −, while that of HO showed an increasing and then decreasing pattern, with a maximum increase by 171.7% at 5 μM Br − . The concentrations of Br and Br2 − (10 −12 − 10 −10 M) were 2 – 3 orders of magnitude higher than SO4 − and HO . Alkaline condition promoted the conversion from SO4 − to HO, and drove the transformation from RBS to HO, resulting in much lower concentrations of RBS at pH 10. Br − at 1 μM and 5 μM decreased the pseudo-first-order reaction rates ( kʹ s) of 15 pharmaceuticals and personal care products (PPCPs) by 15.2 – 73.9%, but increased kʹ s of naproxen and ibuprofen by 13.7 – 57.3% at pH 7. The co-existence of 10 − 1000 μM Cl − with 5 μM Br − further promoted the conversion from SO4 − to HO compared to Br − alone. Bicarbonate consumed SO4 − and HO but slightly affected RBS, while natural organic matter (NOM) exerted scavenging effects on HO and RBS more significantly than SO4 − . This study demonstrated that Br − at fresh water levels significantly altered the radical chemistry of the UV/PDS process, especially for promoting the formation of HO . Graphic abstract: Image, graphical abstract